NON-FORMAL EDUCATION OF EDUCATORS IN MEDIA CENTERS OF LEADING EUROPEAN COUNTRIES: EDUCATIONAL AND METHODOLOGICAL ASPECT - Halyna Horbenko; Yana Fruktova; Oleksandra Hondiul (Borys Grinchenko Kyiv Metropolitan University, 2020)
Media literacy is recognized as a basic, vital skill for European citizens. It must be formed during life, at all stages of personality development. That is why we have chosen the leading European countries such as Finland, Sweden, France, Germany, the United Kingdom and Spain to analyze the current state of media education. Europe should be at the forefront of media literacy, as historically this region of the world has become the cradle of media civilization, a center for coordinating discussions of philosophical, cultural and technical development of the media. The article deals with the analysis of educational and methodical support of the European system of educators' media education. The importance of media education of educators as the greatest agents of direct educational influence on the younger generation, whose media education is a requirement of the time, is revealed. The need for the development of non-formal and informal media education of educators is identified, as the media component can take place in any lesson and in extracurricular activities. Common components of the organization system of this process (participants, content, forms, methods, tools) are identified and educational and methodological resources are described, which are publicly available and can be useful to educators regardless of country of residence, citizenship or language. As a result of the research, we made the following conclusions: specialized centers offer a wide range of short-term training courses for teachers of various topics; forms of professional development in media education of teachers are different (distance courses, trainings, seminars, workshops, conferences, educational films, etc.); modern scientific, educational, methodical literature for teachers is available (monographs, professional journals, lesson plans, information packages); non-formal and informal preparation of teachers for media education activities is diverse in content, forms, means and methods, but remains fragmentary, not systematic, which does not allow to solve our issue comprehensively, and therefore it needs further development and critical analysis.